2014
DOI: 10.1530/rep-13-0444
|View full text |Cite
|
Sign up to set email alerts
|

No association between exposure to perfluorinated compounds and congenital cryptorchidism: a nested case–control study among 215 boys from Denmark and Finland

Abstract: Geographical differences in the occurrence of diseases in male reproductive organs, including malformation in reproductive tract, between Denmark and Finland have been reported. The reason for these differences is unknown, but differences in exposure to chemicals with endocrine-disrupting abilities have been suggested. Among these chemicals are perfluoro-alkylated substances (PFASs), a group of water-and grease-repellent chemicals used in outdoor clothes, cookware, food packaging, and textiles. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 29 publications
(41 reference statements)
2
18
0
Order By: Relevance
“…Evidence of effects on fetal Leydig cell hormone production has led others to hypothesize that PFOS exposure might affect androgen- and insulin-like factor 3 (INSL3)–dependent testicular descent ( Bay et al 2011 ) and scrotal fusion ( Kalfa et al 2009 ). Only one previous study has evaluated the risk of cryptorchidism in relation to PFAS exposure; this study did not observe associations between PFAS level in cord blood and cryptorchidism ( Vesterholm et al 2014 ). However, due to a limited study size of 59 cryptorchidism cases and 108 matched controls, the power to show an association was limited.…”
Section: Introductionmentioning
confidence: 53%
“…Evidence of effects on fetal Leydig cell hormone production has led others to hypothesize that PFOS exposure might affect androgen- and insulin-like factor 3 (INSL3)–dependent testicular descent ( Bay et al 2011 ) and scrotal fusion ( Kalfa et al 2009 ). Only one previous study has evaluated the risk of cryptorchidism in relation to PFAS exposure; this study did not observe associations between PFAS level in cord blood and cryptorchidism ( Vesterholm et al 2014 ). However, due to a limited study size of 59 cryptorchidism cases and 108 matched controls, the power to show an association was limited.…”
Section: Introductionmentioning
confidence: 53%
“…We identified 33 papers that were based upon 28 independent studies reported 89 associations between measured levels of endocrine disrupting chemicals and one or more of the outcomes: cryptorchidism (Hosie et al ., 2000; Longnecker et al ., 2002; Pierik et al ., 2004, 2007; Bhatia et al ., 2005; Damgaard et al ., 2006; Main et al ., 2007; Brucker-Davis et al ., 2008; McGlynn et al ., 2009a; Fenichel et al ., 2012; Chevalier et al ., 2015; Jensen et al ., 2015; Komarowska et al ., 2015; Small et al ., 2009; Trabert et al ., 2012; Vesterholm et al ., 2014; Toft et al ., 2016; Virtanen et al ., 2012); hypospadias (Longnecker et al ., 2002; Bhatia et al ., 2005; Small et al ., 2009; McGlynn et al ., 2009a; Carmichael et al ., 2010; Giordano et al ., 2010; Choi et al ., 2012; Jensen et al ., 2015; Rignell-Hydbom et al ., 2012; Trabert et al ., 2012; Toft et al ., 2016); testicular cancer (Hardell et al ., 2003, 2004; Biggs et al ., 2008; Cohn et al ., 2010; Giannandrea et al ., 2011; McGlynn et al ., 2008; 2009b; Purdue et al ., 2009); and sperm count (Mocarelli et al ., 2011; Axelsson et al ., 2015; Vested et al ., 2013, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Some authors have observed higher levels of the compounds bisphenol A , 176 dibutylin 169 dioxin , 164,173 heptachloroepoxide , 174 hexachlorobenzene , 174 polychlorinated biphenyls 164,173,177 and polybrominateddiphenyl ethers 159,164 among boys (and/or their mothers) who developed cryptorchidism compared to those who did not; however a substantial number of studies (at least some of which were adequately powered to detect an association) have directly evaluated these and other biologically-plausible compounds and found no such association. 56,60,152157,160,163,168,172,178 In some cases, studies have found substantial regional heterogeneity, including conflicting results between countries within the same study. 161,162,164,169 For example, Rantakokko et al 169 observed that maternal exposure to high levels (>0.15ng/g) of dibutylin was associated with increased risk of cryptorchidism in Danish sons (adjusted OR vs. <0.10ng/g: 4.01, 95% CI 1.42–11.33), but was inversely associated in Finnish sons (adjusted OR: 0.16, 95% CI 0.03–0.75).…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%
“…Maternal or childhood direct exposure to endocrine-disrupting chemicals 56,60,152157,159,160,163,164,168,169,172174,176178 …”
mentioning
confidence: 99%